The Placebo Effect in Mental Health: Psychological, Neurobiological, and Ethical Aspects - Dubljanin, Jakša; Radlović, Aleksandar; Nenezić, Nemanja; Biševac, Emir; Mahmutović, Elvis; Safiye, Teodora (Archives of Pharmacy, 2026)
The placebo effect is a psychobiological phenomenon in which patients’ expectations, prior experiences, and social context influence health outcomes, even in the absence of active pharmacological treatment. Key mechanisms include expectancy, verbal suggestion, classical conditioning, and social-contextual factors, underpinned by neurobiological processes involving endogenous opioids, dopamine, and related neural circuits. In mental health and psychotherapy, placebo effects are particularly relevant, as the therapeutic alliance, empathy, and belief in treatment can significantly enhance outcomes. Ethical applications such as open-label and dose-extending placebos preserve patient autonomy while leveraging expectancy and learning to improve clinical results. Recognizing and integrating placebo mechanisms into clinical practice highlights the interaction of psychological, neurobiological, and ethical factors, offering a holistic approach to treatment and enhancing therapy outcomes in conditions like depression, anxiety, and chronic pain.